Airborne Imaging Microwave Radiometer (AIMR). Version 1.0 ... - UCAR/NCAR-Earth Observing Laboratory (UCAR/NCAR - Earth Observing Laboratory, 2011)
This data set includes Airborne Imaging Microwave Radiometer (AIMR) measurements obtained from the NSF/NCAR C-130 aircraft (Tail Number: N130AR) during the Beaufort Arctic Storms Experiment (BASE) in 1994. ...